The Endogenous/Exogenous Nature of South Africa's Money Supply Under Direct and Indirect Monetary Control Measures - Kevin S. Nell (University of Kent, Department of Economics, 1999)
The main purpose of this paper is to describe South Africa's money supply process along several competing, but not mutually exclusive, theoretical paradigms over the period 1966-1997. The most important conclusion to be drawn from the empirical results is that irrespective of the monetary system at the time, the money supply process in South Africa is endogenously determined. The empirical analysis further shows that the inability of the South African Reserve Bank (SARB) to reach predetermined M3 monetary growth targets on a consistent basis since the mid 1980s is the direct result of an endogenous money supply and not, as a previous study claims, because of an unstable M3 velocity. Although the M3 velocity is stable over the whole period 1966-1997, money income determined an endogenous money supply, so that the M3 money supply lost its effectiveness as a leading indicator for monetary policy. The policy implication is that the SARB controlled the M3 money supply indirectly over the period 1980-1997, through an increase in interest rates, and at the potential cost of a slowdown in economic activity.
Keywords: C22; E51; E52; E58; 330; Exogenous/endogenous money supply; M3 velocity; Causality tests; Geldmenge; Geldumlaufgeschwindigkeit; Geldpolitisches Ziel; Kausalanalyse; Südafrika